Antimicrobial Protein Produced by Vaginal Lactobacillus acidophilus that inhibits Gardnerella vaginalis - Alla A. Aroutcheva; Jose A. Simoes; Sebastian Faro (Hindawi Limited, 2001)
Objective: To isolate bacteriocin from a vaginal strain of Lactobacillus acidophilus.